PSYCHOLOGY PRESSURES AND ITS RELATIONSHIP TO DECISION-MAKING AMONG INTERNATIONAL FOOTBALL REFEREES IN IRAQ - Ibrahim, Ahmed Jalal; Hussein, Emad Abbas; Abdulhalim, Saleh Nayef (Universitas Negeri Jakarta, 2026)
Background. Psychological pressure is an inherent characteristic of human performance in situations demanding rapid response and accurate judgment, particularly in the complex and multifaceted world of sports. Research Problem refereeing football is a sporting task that demands a high level of focus, accuracy, and emotional stability, given nature of refereeing decisions, which are made quickly and under influence of numerous factors. These factors include psychological pressures stemming from importance of matches, behavior of players and coaching staff, fan reactions, and constant media scrutiny. Objectives. This research aims to identify level of psychological stress and decision-making skills among international football referees in Iraq, and to reveal nature of relationship between them in light of realities of refereeing in field. Method. The researcher used a descriptive correlational approach, and the research population consisted of 20 officially accredited international referees with Iraqi Football Association during 2025–2026 sports season, selected purposively at a rate of 100%. A 30-item stress scale and a 26-item decision-making scale were used, after their validity and reliability were verified using appropriate scientific methods. Results. Results showed that referees' stress levels were relatively high, while their decision-making abilities were very good. Results also revealed a statistically significant inverse correlation between stress and decision-making, indicating that increased stress leads to a relative decrease in the efficiency of refereeing decisions. Conclusion. International football referees in Iraq suffer from a relatively high level of psychological pressure. The referees have a good level of decision-making. There is a statistically significant inverse correlation between psychological stress and decision-making. Psychological pressures negatively affect speed and accuracy of refereeing decisions during matches.